Enhancing Arabic Speaking Skills Through the Role-Play Method in The Mubtadi Class at Al-Ma'had Al-Lughowy - Acep Hermawan; Dadan Nugraha; Davina Davina; Jimmy Surya Nugraha (UIN Sunan Gunung Djati Bandung, 2025)
This study investigates the effectiveness of the role play method in improving Arabic speaking skills among beginner-level (Mubtadi) students at Al-Ma’had Al-Lughowy. Using a Classroom Action Research (CAR) approach, the research was conducted over two cycles, each consisting of planning, action, observation, and reflection stages. The subjects included 93 second-semester students from the Arabic Language Education Program. Data collection techniques comprised observations, interviews, and speaking tests. The results showed a significant improvement in students’ speaking abilities, including fluency, vocabulary, grammar, and pronunciation. Pre-intervention scores ranged from 40 to 55, while post-intervention scores rose to 60–80, with most students achieving or surpassing the minimum mastery criterion of 75. Students also demonstrated increased confidence, motivation, and participation in speaking activities. These findings confirm that role play is an effective method for enhancing speaking competence and fostering an interactive, student-centered learning environment. The study recommends incorporating role play into Arabic language instruction to improve oral communication skills in a meaningful and engaging way.